Cognitive Profile of Intellectually Gifted Adults: Analyzing the Wechsler Adult Intelligence Scale. (July 2019) - Lang, Margherita; Matta, Michael; Parolin, Laura; Morrone, Cristina; Pezzuti, Lina
The Wechsler Adult Intelligence Scale (WAIS) has been used extensively to study intellectual abilities of special groups. Here, we report the results of an intellectually gifted group on the WAIS-IV. Gifted individuals are people who obtained scores equal to or greater than 2 standard deviations above the mean on an intelligence test. Hence, the current study aims first, to examine mean group performance data of gifted individuals on the WAIS-IV; second, to revalidate the pattern of performance identified in this special group in previous studies (i.e., verbal skills higher than all other abilities); third, to compare scatter measures across intellectual domains with a matched comparison group. A total of 130 gifted individuals (79 males) were administered the full battery and their performance was compared with a matched comparison group. Analyses revealed that gifted group displayed higher scores in all intellectual domains. Contrary to expectations, they showed the highest scores in perceptual reasoning tasks. A multivariate approach revealed that this ability was statistically different from all other domains within the gifted group. Moreover, gifted individuals showed higher discrepancies across intellectual domains than average-intelligence people. Findings have important practical implications to detect intellectual giftedness in adulthood.